THE INTERSECTION OF ARTIFICIAL INTELLIGENCE AND EMPLOYMENT LEGAL RELATIONS: BALACING EMPLOYER INTERESTS WITH FUNDAMENTAL RIGHTS IN AI-DRIVEN EMPLOYMENT PRACTICES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the era of rapid technological advancement, artificial intelligence (hereinafter “AI”) has profoundly transformed various sectors, notably employment. The integration of AI in employment practices represents a significant paradigm shift, enhancing efficiencies but also introducing substantial challenges. This integration poses complex legal issues, particularly in balancing employer interests with employees' fundamental rights, in particular to privacy. As of August 1, 2024, the European Artificial Intelligence Act (hereinafter "AI Act") was enacted. This legislation introduces a risk-based framework that mandates specific responsibilities for both providers and deployers of AI systems. Within the context of employment legal relationships and the integration of various AI systems therein, it is crucial to conduct a thorough analysis of the interplay between the General Data Protection Regulation and the stipulations of the AI Act. This article examines the legal frameworks that regulate rights to privacy and AI-driven employment practices, emphasizing the imperative to reconcile employer objectives—such as productivity and cost-efficiency—with employees' rights to privacy, non-discrimination, and equitable treatment. Through a detailed comparative analysis of extant legislation and case law, this study identifies deficiencies in current legal protections and advocates for a framework that ensures AI systems in employment conform to fairness and human rights principles. The article argues for a proactive legislative approach that not only addresses current challenges but also anticipates future ethical and legal issues arising from advancements in AI technology.